A Systematic Review of the Impact of Technological Advancements on Modern Accounting Practices - Sulaiman Taiwo Hassan; Abdullahi Ya'u Usman (Marasofi International Media and Publishing (MIMP), 2025)
With the emergence of Industry 4.0, advanced technologies such as artificial intelligence (AI), data analytics, and automation have profoundly transformed the field of accounting. This paper presents a systematic review of recent literature to investigate the evolving landscape of accounting practices influenced by these technological advancements. The study emphasizes the impact of information technology and data analytics on accounting processes and managerial decision-making. Employing a rigorous systematic literature review methodology, relevant academic sources and premier journals were examined under strict inclusion and exclusion criteria. Findings reveal a notable rise in the integration of IT and data analytics within the accounting profession, alongside challenges related to implementation, including the necessity for specialized training and organizational adaptability. The paper concludes by advocating for the creation of comprehensive training programs to support accounting professionals in navigating technological transitions. This review aims to enhance the understanding of current trends in accounting and to guide future research directions in this evolving domain.